A bio-mechanical process for cellulose nanofiber production – Towards a greener and energy conservation solution. (15th March 2019) - Liu, Xiuyu; Jiang, Yan; Song, Xueping; Qin, Chengrong; Wang, Shuangfei; Li, Kecheng
Highlights: An enzyme-mechanical process for nanofiber production saved 60% mechanical energy. Enzyme promoted higher yield and more uniform nano-sized fibers. The nanofilms were denser, more transparent, with high thermal stability. The bio-mechanical process is readily scalable and can be economically viable. Abstract: Enzyme pretreatment prior to mechanical grinding in cellulose nanofibers production were fully explored in order to save mechanical energy and to find an alternative to chemical treatment, thus reducing the environmental impact of the process. Grinding energy was determined in terms of total energy, effective energy, and was related to nanofiber yield. Fiber morphology, crystalline and chemical structures were analyzed to reveal the mechanisms behind enzyme actions. The results showed that with enzyme pretreatment, the effective energy was reduced by 60%, and yield of nanofibers was increased by 76%. With enzyme pretreatment, nanofibers were smaller and more uniform in diameter, which resulted in more transparent nanofilms. The mechanical strength of nanofilm was decreased slightly when enzyme dosage is high, however, in any cases, nanofibers remained high thermal stability. Therefore, this bio-mechanical process can be a commercially viable, energy-effective nanofibers manufacturing process with less environmental impact.